2000
DOI: 10.1016/s0893-133x(99)00141-4
|View full text |Cite
|
Sign up to set email alerts
|

Topographically Based Search for an “Ethogram” Among a Series of Novel D4 Dopamine Receptor Agonists and Antagonists

Abstract: terms of individual topographies of behavior within the natural rodent repertoire, as evaluated using ethologically based approaches. Among the D 4 antagonists, neither L-745,870 (0.0016-1.0 mg/kg) nor .0 mg/kg) influenced any behavior; whereas, 019;870; D 4 agonists; CP-226,269; PD 168077; Ethological assessment (Missale et al. 1998;Neve and Neve 1997;Waddington et al. 1995Waddington et al. , 1998. In particular, any behavioral role for the D 4 receptor (Van Tol et al. 1991) remains poorly understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…This finding is consistent with previous observations that D 4 antagonists given at moderate doses lacked effects on spontaneous behaviors in intact rats or mice (Clifford and Waddington 2000). Involvement of D 2 receptors in the antihyperactivity effects of D 4 antagonists seems unlikely in view of the low potency of all tested agents at this DA receptor subtype and, moreover, since eticlopride, an antagonist that binds preferentially to D 2 receptors, did not antagonize motor hyperactivity in the 6-OHDA lesioning model (Zhang et al 2001b).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous observations that D 4 antagonists given at moderate doses lacked effects on spontaneous behaviors in intact rats or mice (Clifford and Waddington 2000). Involvement of D 2 receptors in the antihyperactivity effects of D 4 antagonists seems unlikely in view of the low potency of all tested agents at this DA receptor subtype and, moreover, since eticlopride, an antagonist that binds preferentially to D 2 receptors, did not antagonize motor hyperactivity in the 6-OHDA lesioning model (Zhang et al 2001b).…”
Section: Discussionsupporting
confidence: 92%
“…Table 1) failed to alter pramipexole-induced PE or yawning. Although Ro 61-6270 has not been characterized extensively (Clifford and Waddington, 2000), L-745,870 has been shown to possess favorable pharmacokinetics (0.3 mg/kg p.o. is thought to be sufficient to occupy ϳ90% of D 4 receptors; Patel et al, 1997) and has been shown to inhibit PD-168,077-and PIP3EA-induced PE at a dose of 1.0 mg/kg Melis et al, 2006), suggesting that the doses used in the current studies were sufficient to block D 4 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…ABT-724 had no effect in concentrations up to 10 M, whereas sildenafil induced a complete relaxation with an EC 50 ϭ 44.37 Ϯ 11.2 nM (see supporting information). Apomorphine was also inactive in this assay in concentrations up to 10 M, consistent with previous data in the literature using rat cavernosal strips (25).…”
Section: Figmentioning
confidence: 92%
“…D 3 receptors are highly expressed in the island of Calleja, hypothalamus, and thalamus, and are an attractive target for the potential treatment of drug abuse in view of the inhibition of cocaine-seeking behavior induced by the partial D 3 agonist BP897 (9). On the other hand, the D 4 receptor is more abundant in the frontal cortex, hippocampus, amygdala, and hypothalamus, but pharmacological studies have failed to reveal any psychopharmacological effect in rats (10). The therapeutic effect of clozapine in psychotic patients that do not respond to classical antipsychotic agents like haloperidol prompted the hypothesis that D 4 receptors may be responsible for the antipsychotic activity as clozapine is a preferential D 4 antagonist (11).…”
mentioning
confidence: 99%